The avowal of difference : queer Latino American narratives - Sifuentes-Jáuregui, Ben (Genders in the global south., 2014)
Discusses how theories of queer performativity, as articulated within the US Academy, are unable to capture the whole of Latino American queer subjectivity and experience. The Avowal of Difference explores the potentialities and limitations that queer theory offers in the context of Latino American texts and subjects. Ben. Sifuentes-Jáuregui contrasts Latino American sexual genealogies with the Anglo-European "coming out" narrative-and interrogates the centrality of the "coming out" story as the regulating metaphor for gay, lesbian, or queer identities. In its place, the book looks at other strategies-from silence to circumlocution, from disavowal to indifference-to theorize queer subject formation in a Latino American cultural context. The analysis of texts by José Lezama Lima, Luis Zapata, Manuel Puig, Severo Sarduy, Junot Díaz, and others offers a comparative approach to understanding how queer sexualities are shaped and written in other cultural contexts. Ben. Sifuentes-Jáuregui is Associate Professor of American Studies and Comparative Literature at Rutgers University. He is the author of Transvestism, Masculinity, and Latin American Literature: Genders Share Flesh.